СОПОСТАВИТЕЛЬНЫЙ АНАЛИЗ ФРАЗЕОЛОГИЧЕСКИХ ЕДИНИЦ, ВЫРАЖАЮЩИХ ВОЗРАСТ ЧЕЛОВЕКА В УЗБЕКСКОМ И РУССКОМ ЯЗЫКАХ («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
Phraseological fund of any language is known to be the most expressive way of conveying singularity of its national culture. The aim of the following research is to reveal universal and unique in the semantics of the phraseological units expressing childhood age in the Uzbek and Russian languages.
Keywords: anthropocentric approach, age, semantic analysis, phraseological description, dictionary definition, nuclear seme, component structure, additional seme, meliorative esteem, integral seme.